Consciousness: New Concepts and Neural Networks - Zhao, Tong; Zhu, Yiqian; Tang, Hailiang; Xie, Rong; Zhu, Jianhong; Zhang, John H. (Frontiers in Cellular Neuroscience, 2019)
The definition of consciousness remains a difficult issue that requires urgent understanding and resolution. Currently, consciousness research is an intensely focused area of neuroscience. However, to establish a greater understanding of the concept of consciousness, more detailed, intrinsic neurobiological research is needed. Additionally, an accurate assessment of the level of consciousness may strengthen our awareness of this concept and provide new ideas for patients undergoing clinical treatment of consciousness disorders. In addition, research efforts that help elucidate the concept of consciousness have important scientific and clinical significance. This review presents the latest progress in consciousness research and proposes our assumptions with regard to the network of consciousness.